Initial psychometric evidence of a brief measure of cancer worry [Evidencias psicométricas iniciales de una medida breve sobre preocupación por el cáncer] - Caycho-Rodríguez, Tomás (2018)
ABSTRACT Objective: The cancer worry is associated with preventive behaviors for the detection of this disease; However, there is no instrument with evidence of validity and reliability to measure this construct in Latin American countries, including Peru. The objectives of this study were to evaluate the evidence of validity based on the internal structure and reliability of the Cancer Worry Scale (CWS) in a sample of people without cancer diagnosis with a family history of cancer. Method: It counted with the participation of 215 healthy people with a family history of cancer who attended the outpatient service of two public and private health institutions in the city of Chimbote with an average age of 42.10 years (SD = 14.05). For the collection of information, an ad hoc sociodemographic record and the Cancer Worry Scale were used. Results: The one-dimensional model presented a good fit of the data (SBχ2 (8) = 14.39, SB χ2 / df = 1.79, CFI = 0.991, SRMR = 0.025, RMSEA = 0.061 [IC90%: 0.0000.111], AIC = 47.701) and adequate reliability (ω corrected = 0.90; IC95%: 0.88-0.92). Conclusion: It is concluded that the CWS presents adequate psychometric properties, being a measure that provides valid and reliable interpretations of the cáncer worry in the peruvian context.